Light-assisted zinc-air battery self-powered sensor for gallic acid detection and preparation method thereof

Through the self-energized sensor of the photo-assisted zinc air battery, the detection of gallic acid is solved by using the AgBr/CuBi2O4 composite material, and the problems of high detection limit and poor reproducibility in the prior art are solved, and the detection effect of high sensitivity and low detection limit is achieved.

CN116148322BActive Publication Date: 2025-02-14CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211490795.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2025-02-14
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

The prior art is difficult to accurately and efficiently detect the antioxidant properties of polyphenol-based gallic acid. The traditional methods have problems such as high detection limit, poor reproducibility, low anti-interference ability, expensive equipment and complex operation.

Method used

The self-energized sensor of the photo-assisted zinc air battery is used to detect gallic acid by using AgBr/CuBi2O4 composite material as the photocathode, and self-energized sensing is achieved by using photoelectrochemical reactions.

Benefits of technology

It realizes gallic acid detection with high sensitivity, low detection limit and wide detection range, which is simple to operate, low cost, high sensitivity, wide linear range and low detection limit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116148322B_ABST
    Figure CN116148322B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of photoelectrochemical detection, and specifically relates to a light-assisted zinc-air battery self-powered sensor for gallic acid detection and a preparation method thereof. First, CuBi2O4 is electro-deposited on a FTO substrate, and then AgBr / CuBi2O4 is prepared by chemical deposition. A zinc sheet is used as an anode and AgBr / CuBi2O4 is used as a cathode to construct a light-assisted zinc-air battery-based self-powered sensor. The photoelectric material of the present invention is a composite material of AgBr and CuBi2O4. By combining the zinc-air battery into the self-powered sensor, the output voltage can be significantly improved, and the voltage is further enhanced under the auxiliary effect of light to amplify the detection signal. The present invention broadens the application of the composite material of AgBr and CuBi2O4 in light-assisted zinc-air batteries, and also provides a new strategy for the detection of antioxidant capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photoelectrochemical detection, and in particular relates to a light-assisted zinc-air battery self-powered sensor for gallic acid detection and a preparation method thereof. Background Art

[0002] The continuous contact between the human body and the outside world will continuously produce free radicals. When the concentration of oxidative active substances is too high, the body's oxidation and anti-oxidation are out of balance, and the body is in a state of oxidative stress. At this time, oxidative active substances such as free radicals will damage macromolecules in cells, impair cell functions and cause a series of diseases. Antioxidants can effectively overcome their harm. Polyphenols are a mixture of secondary metabolites widely present in plants, especially in terms of free radical scavenging ability, showing good antioxidant properties. They have become a natural antioxidant with broad development prospects that has attracted much attention in recent years. Gallic acid (GA) and its derivatives are a type of polyphenols that are widely distributed in the plant kingdom and have antioxidant properties. Gallic acid (GA) has become a reliable indicator for quality control in pharmaceutical companies. Therefore, in market supervision, finding a convenient detection tool is crucial for both producers and consumers.

[0003] Traditional antioxidant capacity detection methods mainly include electrochemical method, spectroscopy and chromatography. Among them, although the electrochemical method has a low detection limit, small dosage and simple operation, the electrode is easily contaminated by the product, the result reproducibility is poor, and the anti-interference ability is low. Chromatographic and spectral instruments are expensive and complicated to operate, requiring professional personnel to operate, and can only detect single-component antioxidants, and cannot truly reflect the synergistic effect between antioxidants. Chromatographic and spectral methods cannot give accurate results. Most natural Chinese herbal extracts have a certain color and contain multiple chemical components, which will also affect the detection. The above conventional detection methods are difficult to accurately and efficiently evaluate their antioxidant properties. In view of this, it is urgent to establish a low-cost, simple and fast, highly sensitive and reproducible method to overcome the above shortcomings.

[0004] Self-powered sensor (SPS) is a sensing system based on the conversion between chemical energy and electrical energy. It provides energy for electrochemical sensing by constructing a suitable battery system and uses the direct or indirect participation of the analyte in the electrode reaction to cause changes in the battery output signal. Unlike the traditional electrochemical sensor energy supply method, this new sensing system provides energy for the sensing process through spontaneous chemical reactions at the anode and cathode. However, most self-powered sensors have defects such as low output voltage, low output power, and large micro-amplification current, requiring more complex and expensive instruments for detection, which limits the development of self-powered sensors. Metal-air batteries generate electricity through the redox reaction between metal anodes and oxygen. Zinc-air batteries have attracted more and more attention due to their high energy density, use of oxygen in the environment as fuel, low cost, and environmental friendliness. Therefore, introducing high-energy-density zinc-air battery systems into self-powered sensors will establish a new generation of promising electrochemical detection equipment. There have been no reports on the establishment of a self-powered sensing platform for photoelectrochemical detection of gallic acid based on light-assisted zinc-air battery devices. Summary of the invention

[0005] The present invention aims to provide a method for constructing a light-assisted zinc-air battery self-powered sensor for sensitive detection of gallic acid, which has the advantages of high sensitivity, low detection limit, wide detection range, etc. A self-powered sensor is constructed based on AgBr / CuBi2O4 composite material for the detection of gallic acid. The preparation process of the sensor is simple and the cost is low. The test results show that the sensor has high sensitivity and low detection limit.

[0006] The technical solution of the present invention:

[0007] The first object of the present invention is to provide a method for preparing a light-assisted zinc-air battery self-powered sensor, the preparation method comprising the following steps:

[0008] (1) Preparation of AgBr / CuBi2O4 composite materials:

[0009] Bi(NO3)3·5H2O and Cu(NO3)2·3H2O were dissolved in HNO3 with a mass concentration of 9-12% to prepare a mixed solution containing Bi(NO3)3 and Cu(NO3)2, in which the concentration ratio of Bi(NO3)3 to Cu(NO3)2 was 2:1. 10-50ml of the mixed solution was placed in an electrolytic cell, with the FTO electrode as the working electrode, the platinum electrode as the counter electrode, and the silver / silver chloride electrode as the reference electrode. The electrodeposition voltage was set at -0.5Vvs Ag / AgCl, and the electrodeposition was started. After 150-200s of electrodeposition under magnetic stirring, the surface of the FTO electrode turned dark brown, and the electrodeposition stopped. The FTO electrode was taken out, washed with ultrapure water to remove the residual acid, and then dried naturally in the air. The FTO electrode was then placed in a muffle furnace and annealed at 450-550℃ for 1.5-2h, with a heating rate of 2-5℃ / min. After cooling to room temperature, a black-brown CuBi2O4 layer was deposited on the FTO surface to obtain a CuBi2O4 / FTO electrode; then, AgBr nanoparticles were assembled on the surface of the CuBi2O4 / FTO electrode by chemical deposition. The specific steps were as follows: the prepared CuBi2O4 / FTO electrode was immersed in an aqueous solution containing 1mM KBr and 1mM AgNO3 for 1 to 3 hours, then rinsed with ultrapure water and placed in an oven at 80 to 100°C for 3-9 hours to successfully prepare an AgBr / CuBi2O4 composite material, and the composite material was used as the photocathode of a light-assisted zinc-air battery, namely, an AgBr / CuBi2O4 / FTO electrode.

[0010] (2) Preparation of light-assisted zinc-air battery self-powered sensor:

[0011] Use a 200-500W xenon lamp with a 420nm UV filter as the irradiation source, light intensity: 15-25mW cm -2 , the zinc sheet is used as the anode and the AgBr / CuBi2O4 / FTO electrode is used as the photocathode. During discharge, the zinc anode is oxidized to zinc ions, eventually forming zinc oxide and releasing electrons to the external circuit. The photocathode undergoes an oxygen reduction reaction under light conditions to obtain electrons. Among them, the distance between the zinc sheet anode and the photocathode material modified FTO electrode is 15 to 25 mm. The output voltage of the sensor is recorded by collecting the open circuit voltage-time curve under light irradiation.

[0012] Furthermore, in the mixed solution of Bi(NO3)3 and Cu(NO3)2, the concentrations of Bi(NO3)3 and Cu(NO3)2 are 8mM and 4mM, respectively.

[0013] The second object of the present invention is to provide a light-assisted zinc-air battery self-powered sensor prepared by the above preparation method.

[0014] The third object of the present invention is to provide an application of the light-assisted zinc-air battery self-powered sensor prepared by the above preparation method in the photoelectrochemical method for gallic acid detection, and the steps for gallic acid detection are as follows:

[0015] S1. Prepare phosphate-buffered saline (PBS) buffer solution;

[0016] S2, preparing PBS buffer solutions containing different concentrations of gallic acid and 0.1 mol / L;

[0017] Accurately weigh gallic acid and prepare it with deionized water to 1.0×10 -2 mol / L standard solution, the standard solution was diluted step by step with deionized water to obtain gallic acid standard solutions of different concentrations, the concentration range was 1.0×10 - 6 mol / L~5.0×10 -3 mol / L;

[0018] S3. Drawing of standard curve:

[0019] A series of gallic acid with known concentrations were dropped onto the prepared AgBr / CuBi2O4 / FTO electrode surface and dried naturally at room temperature;

[0020] Using PBS buffer solution as the electrolyte, the open circuit voltage was tested under light to obtain a series of concentration-voltage correspondences, and then the standard curve of gallic acid was obtained. The linear relationship between the open circuit voltage after adding gallic acid and the logarithm of the gallic acid concentration was established, and the corresponding linear regression equation was obtained.

[0021] S4. Actual sample testing:

[0022] After filtering and removing impurities from the sample, the pH is adjusted, and the test is performed according to the above step S3 to obtain the open circuit voltage value. The obtained open circuit voltage value is calculated using the linear regression equation obtained in step S3 to obtain the concentration of gallic acid in the sample.

[0023] Furthermore, in step S3, the pH of the PBS buffer solution is 7.4, and its concentration is 0.1 mol / L.

[0024] Furthermore, the minimum detection limit of the gallic acid solution concentration detected by the light-assisted zinc-air battery self-powered sensor is 8.7×10 -7 mol / L.

[0025] The beneficial effects of the present invention are:

[0026] The present invention prepares the composite AgBr / CuBi2O4 as the photocathode material, successfully establishes a photoelectrochemical sensing platform, and establishes a photoelectrochemical detection method of gallic acid, the characteristics and advantages of which are described as follows:

[0027] (1) The present invention solves the bottleneck problems of low output voltage and low output power of self-powered sensors by introducing zinc-air batteries into self-powered sensors, and further improves the output signal of the sensor by accelerating the slow ORR reaction of light-assisted zinc-air batteries. P-type semiconductor CuBi2O4 is prepared by electrodeposition, and then compounded with AgBr by chemical deposition to significantly improve the photoelectric performance, thereby serving as a photocathode of light-assisted zinc-air batteries. The electrostatic adsorption of AgBr / CuBi2O4 on gallic acid anions affects electron transfer, and when oxygen reduction reaction occurs on the electrode surface, gallic acid anions easily react with oxygen to generate quinone substances, causing the output signal to decrease, thereby realizing the detection of gallic acid.

[0028] (2) Compared with traditional detection methods, the photoelectrochemical detection method proposed in the present invention has the advantages of simple and flexible operation, simple instrumentation, high sensitivity, wide linear range, low detection limit, and low detection cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a brief flow chart of the preparation of the sensor in the invention and the detection of gallic acid;

[0030] Figure 2 It is the optimization of chemical deposition time of AgBr;

[0031] Figure 3 It is the comparison of open circuit voltage response values ​​of AgBr, CuBi2O4 monomer materials and AgBr / CuBi2O4 composite materials;

[0032] Figure 4 This is the open circuit voltage diagram of different concentrations of gallic acid. The concentration of gallic acid changes from top to bottom in terms of open circuit voltage (a) 1×10 -6 mol / L, (b)5×10 -5 mol / L, (c)1×10 -5 mol / L, (d)5×10 -4 mol / L, (e)1×10 -4 mol / L, (f)5×10 -3 mol / L;

[0033] Figure 5 It is the standard curve of open circuit voltage after adding gallic acid and the logarithm of gallic acid concentration. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below with reference to the embodiments.

[0035] Example 1

[0036] like Figure 1 As shown, a light-assisted zinc-air battery self-powered sensor is prepared using zinc sheet as anode and AgBr / CuBi2O4 as photocathode to form a self-powered system for gallic acid detection.

[0037] The preparation method of the light-assisted zinc-air battery self-powered sensor comprises the following steps:

[0038] (1) Preparation of AgBr / CuBi2O4 composite materials:

[0039] Bi(NO3)3·5H2O and Cu(NO3)2·3H2O were dissolved in 200mL of 10% HNO3 to prepare a mixed solution containing 8mMBi(NO3)3 and 4mM Cu(NO3)2. 10mL of the mixed solution was placed in an electrolytic cell with a FTO electrode as the working electrode, a platinum electrode as the counter electrode, and a silver / silver chloride electrode as the reference electrode. The electrodeposition voltage was set at -0.5V vs Ag / AgCl, and electrodeposition was started. After 200s of electrodeposition under magnetic stirring, the surface of the FTO electrode turned dark brown, and the electrodeposition stopped. The FTO electrode was taken out, washed with ultrapure water to remove the residual acid, and then dried naturally in the air. The FTO electrode was then placed in a muffle furnace and annealed at 550℃ for 2h with a heating rate of 5℃ / min. After cooling to room temperature, a dark brown CuBi2O4 layer was deposited on the FTO surface to obtain a CuBi2O4 / FTO electrode; then AgBr nanoparticles were assembled on the surface of the CuBi2O4 / FTO electrode by chemical deposition. Specifically, the prepared CuBi2O4 / FTO electrode was immersed in an aqueous solution containing 1mM KBr and 1mM AgNO3 for 2 hours, then rinsed with ultrapure water and dried in an oven at 90°C for 6 hours;

[0040] (2) Preparation of light-assisted zinc-air battery self-powered sensor:

[0041] A 300 W xenon lamp with a 420 nm UV filter was used as the irradiation source (light intensity: 20 mW cm -2 ), the zinc sheet is used as the anode, and the AgBr / CuBi2O4 / FTO electrode is used as the photocathode. During discharge, the zinc anode is oxidized to zinc ions, and finally zinc oxide is formed and releases electrons to the external circuit. The photocathode undergoes an oxygen reduction reaction under light conditions to obtain electrons. The distance between the zinc sheet and the photocathode material modified FTO electrode is 20 mm;

[0042] (3) Drawing of standard curve:

[0043] Prepare gallic acid solution. Accurately weigh a certain amount of gallic acid and use deionized water to prepare 1.0×10 -2 mol / L standard solution, the standard solution was diluted step by step with deionized water to obtain a series of gallic acid standard solutions with different concentrations; in the self-powered sensor based on light-assisted zinc-air battery, the zinc sheet was used as the anode, AgBr / CuBi2O4 was used as the cathode, and the distance between the zinc sheet and the photocathode material modified FTO electrode was 20 mm. A self-powered system was formed to detect gallic acid. Figure 4 As shown, the concentration of gallic acid is as follows from top to bottom according to the peak value of the curve:

[0044] 1×10 -6 mol / L,5×10 -5 mol / L,1×10 -5 mol / L,5×10 -4 mol / L,1×10 -4 mol / L,5×10 - 3 mol / L,1×10 -9 mol / L

[0045] The light-assisted zinc-air battery self-powered system was placed in a series of gallic acid concentrations (1×10 -6 mol / L,5×10 -5 mol / L,1×10 -5 mol / L,5×10 -4 mol / L,1×10 -4 mol / L,5×10 -3 mol / L) in a buffer solution containing 0.1 mol / L PBS with a pH of 7.4, with PBS buffer solution as the electrolyte; then a linear relationship between the open circuit voltage after the addition of gallic acid and the logarithm of the gallic acid concentration was established, and the corresponding linear regression equation was obtained: OCV (V) = -0.2442log C (μmol / L) + 1.8656, with a correlation coefficient (R) of 0.98006; the detection range of the linear regression equation was 1.0×10 -6 ~5.0×10 -3 mol / L, the minimum detection limit is 8.7×10 -7 mol / L.

[0046] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a light-assisted zinc-air battery self-powered sensor, characterized in that: The preparation method steps are as follows: (1) Preparation of AgBr / CuBi2O4 composite materials: Dissolve Bi(NO3)3·5H2O and Cu(NO3)2·3H2O in HNO3 with a mass concentration of 9-12% to prepare a mixed solution containing Bi(NO3)3 and Cu(NO3)2, wherein the concentration ratio of Bi(NO3)3 to Cu(NO3)2 in the mixed solution is 2:1; place 10-50ml of the mixed solution in an electrolytic cell, with a FTO electrode as the working electrode, a platinum electrode as the counter electrode, and a silver / silver chloride electrode as the reference electrode; set the electrodeposition voltage at -0.5Vvs Ag / AgCl, and start electrodeposition; after 150-200s of electrodeposition under magnetic stirring, the surface of the FTO electrode turns dark brown, and the electrodeposition stops; the FTO electrode is taken out, washed with ultrapure water to remove residual acid, and then dried naturally in the air; the FTO electrode is then placed in a muffle furnace and annealed at 450-550°C for 1.5-2h, with a heating rate of 2-5°C / min; after cooling to room temperature, a dark brown CuBi2O4 layer is deposited on the FTO surface to obtain a CuBi2O4 / FTO electrode; then, AgBr nanoparticles are assembled on the surface of the CuBi2O4 / FTO electrode by chemical deposition, and the specific steps are as follows: the prepared CuBi2O4 / FTO electrode is immersed in a solution containing 1mM KBr and 1mM AgBr / CuBi2O4 composite material was successfully prepared by immersing in an aqueous solution of AgNO3 for 1 to 3 hours, then rinsing with ultrapure water and placing in an oven at 80 to 100 °C for 3 to 9 hours. The composite material was used as the photocathode of light-assisted zinc-air batteries, namely, AgBr / CuBi2O4 / FTO electrode. (2) Preparation of light-assisted zinc-air battery self-powered sensor: Use a 200-500W xenon lamp with a 420nm UV filter as the irradiation source, light intensity: 15-25mW cm -2 , the zinc sheet is used as the anode and the AgBr / CuBi2O4 / FTO electrode is used as the photocathode; during discharge, the zinc anode is oxidized into zinc ions, eventually forming zinc oxide and releasing electrons to the external circuit, and the photocathode undergoes oxygen reduction reaction under light conditions to obtain electrons; wherein, the distance between the zinc sheet anode and the photocathode material modified FTO electrode is 15 to 25 mm.

2. The method for preparing a light-assisted zinc-air battery self-powered sensor according to claim 1, characterized in that: In the mixed solution of Bi(NO3)3 and Cu(NO3)2, the concentrations of Bi(NO3)3 and Cu(NO3)2 are 8mM and 4mM respectively.

3. A light-assisted zinc-air battery self-powered sensor prepared by the preparation method according to any one of claims 1 to 2.

4. Application of the light-assisted zinc-air battery self-powered sensor prepared by the preparation method according to any one of claims 1-2 in the detection of gallic acid by photoelectrochemical method, characterized in that: The steps for gallic acid detection are as follows: S1. Prepare phosphate-buffered saline (PBS) buffer solution; S2, preparing PBS buffer solutions containing different concentrations of gallic acid and 0.1 mol / L; Accurately weigh gallic acid and prepare it with deionized water to 1.0×10 -2 mol / L standard solution, the standard solution was diluted step by step with deionized water to obtain gallic acid standard solutions of different concentrations, the concentration range was 1.0×10 -6 mol / L~5.0×10 -3 mol / L; S3. Drawing of standard curve: A series of gallic acid with known concentrations were dropped onto the prepared AgBr / CuBi2O4 / FTO electrode surface and dried naturally at room temperature; Using PBS buffer solution as the electrolyte, the open circuit voltage was tested under light to obtain a series of concentration-voltage correspondences, and then the standard curve of gallic acid was obtained. The linear relationship between the open circuit voltage after adding gallic acid and the logarithmic value of gallic acid concentration was established, and the corresponding linear regression equation was obtained. S4. Actual sample testing: After filtering and removing impurities from the sample, the pH is adjusted, and the test is performed according to the above step S3 to obtain the open circuit voltage value. The obtained open circuit voltage value is calculated using the linear regression equation obtained in step S3 to obtain the concentration of gallic acid in the sample.

5. The application of the light-assisted zinc-air battery self-powered sensor according to claim 4 in the photoelectrochemical method for gallic acid detection, characterized in that: In step S3, the pH of the PBS buffer solution is 7.4 and its concentration is 0.1 mol / L.

6. The use of the light-assisted zinc-air battery self-powered sensor according to claim 5 for the detection of gallic acid by photoelectrochemical method, characterized in that: The minimum detection limit of the gallic acid solution concentration detected by the light-assisted zinc-air battery self-powered sensor is 8.7×10 -7 mol / L.

Citation Information

Patent Citations

  • Method for detecting chlorpyrifos based on photoelectrochemical sensor

    CN110487868A

  • Gold nanoparticle-based plasma resonance enhanced electrochemical luminescence sensor for detecting 1-(2,6-dichlorophenyl)-2-indolinone and preparation method of sensor

    CN112630279A